2012
DOI: 10.1051/kmae/2012011
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological and anatomical responses ofVallisneria natansto nitrogen and phosphorus enrichment

Abstract: Here, we describe an experiment using four nitrogen (N) and phosphorus (P) concentrations to investigate the effects of nutrient enrichment on the submersed macrophyte Vallisneria natans (tape grass) grown in a sand culture medium. The objective of this study was to examine the influence of nutrient enrichment in the water column on V. natans, especially with regard to anatomical structures. The results showed both the absolute growth rate (AGR) and intrinsic efficiency of light energy conversion of PSII (Fv/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 51 publications
(53 reference statements)
1
9
0
6
Order By: Relevance
“…observation). Similarly, several authors suggest observed declines in macrophytes in other systems was a direct effect of increased NO x -N (Burkholder et al 1992;Burkholder et al 1994;Wang et al 2012), suggesting closer investigation of this phenomenon is warranted. Burkholder et al (1992) report that Zostera marina (eelgrass) exhibited highly negative physiological effects (even death) when dosed with 0.05, 0.1 and 0.5 mg L -1 NO x -N. Although a marine species, this plant shows extreme sensitivity to increased nitrate evidenced through loss of carbon storage in roots unrelated to shading by algae.…”
Section: Evidence Of Direct Effects Of Nitrate On Savmentioning
confidence: 97%
See 4 more Smart Citations
“…observation). Similarly, several authors suggest observed declines in macrophytes in other systems was a direct effect of increased NO x -N (Burkholder et al 1992;Burkholder et al 1994;Wang et al 2012), suggesting closer investigation of this phenomenon is warranted. Burkholder et al (1992) report that Zostera marina (eelgrass) exhibited highly negative physiological effects (even death) when dosed with 0.05, 0.1 and 0.5 mg L -1 NO x -N. Although a marine species, this plant shows extreme sensitivity to increased nitrate evidenced through loss of carbon storage in roots unrelated to shading by algae.…”
Section: Evidence Of Direct Effects Of Nitrate On Savmentioning
confidence: 97%
“…Been (Ni 2001). The most definitive observations of inhibition were in the form of shrinkage of arenchyma tissues and disappearance of starches and chloroplasts observed in increased NO x -N and NH 4 -N concentration treatments of Vallisneria natans (Wang et al 2012.). It is important to note that ammonia, whether sourced from high concentrations in water or derived (via intracellular nitrate reduction) from elevated nitrate availability to SAV is the source of toxicity.…”
Section: Evidence Of Direct Effects Of Nitrate On Savmentioning
confidence: 97%
See 3 more Smart Citations